Inverse Design of High Absorption Thin‐Film Photovoltaic Materials. Issue 1 (27th August 2012) - Yu, Liping; Kokenyesi, Robert S.; Keszler, Douglas A.; Zunger, Alex
<x xml:space="preserve">Abstract</x> The "spectroscopic limited maximum efficiency" metric is applied to identify materials design principles leading to high absorption for application in very thin film photovoltaic devices. Several Cu‐V‐VI materials exhibit much stronger solar absorption than CuInSe2, confirmed by our coupled experiment. A general trend on the fundamental factors driving strong absorption in these materials is revealed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>